Determinants of market competitiveness in an environmentally sustainable tourism industry of Masbro Village / Nurun Mursyidah Md Noh - Md Noh, Nurun Mursyidah (Bachelor Of Business Administrations (Hons) Marketing, 2018)
Homestay tourism emphasises on the ecotourism and community-based products and services, in which visitor stay with the foster families and get involved with the normal daily activities in order to experience the lifestyle and local culture. Receiving excellent service will reinforce the loyalty of current visitors and increase the prospect of attracting new ones (Albacete-Saez Fuentes-Fuentes& Llorens-Motes 2007 Erdil &Kalkan, 2010 Jamaluddin, Hanafian, & Zulkify 2013)